2009
DOI: 10.1002/art.24600
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional polymorphism in the IRF5 region with systemic sclerosis in a Japanese population

Abstract: Objective. Interferon regulatory factor 5, an established susceptibility factor for systemic lupus erythematosus (SLE), plays a role in type I interferon and proinflammatory cytokine induction. A recent study showed association of a functional single-nucleotide polymorphism (SNP) in intron 1 of IRF5, rs2004640, with systemic sclerosis (SSc) in a European French population. We undertook the present study to determine whether IRF5 polymorphisms are also associated with a predisposition to SSc in Japanese.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 15 publications
1
62
0
Order By: Relevance
“…The interferon regulatory factor 5 (IRF5) is a transcription factor that mediates activation of interferon and the immune system (1,2). Recently, an association ofthe IRF5 polymorphism with SSc was reported in Caucasians populations of Europe and North America, as well as in Japanese populations (3)(4)(5)(6). However, genetic heterogeneity in different ethnic populations may significantly impact the complex trait of SSc and SSc clinical features.…”
Section: Received September 10 2014 -Accepted October 10 2014mentioning
confidence: 99%
“…The interferon regulatory factor 5 (IRF5) is a transcription factor that mediates activation of interferon and the immune system (1,2). Recently, an association ofthe IRF5 polymorphism with SSc was reported in Caucasians populations of Europe and North America, as well as in Japanese populations (3)(4)(5)(6). However, genetic heterogeneity in different ethnic populations may significantly impact the complex trait of SSc and SSc clinical features.…”
Section: Received September 10 2014 -Accepted October 10 2014mentioning
confidence: 99%
“…Although how the TLR4 signaling pathway contributes to SSc pathogenesis remains enigmatic, it is interesting that several independent case-control and genome-wide association studies identify IFN regulatory factor 5 (IRF5), a member of the IFN regulatory factor (IRF) family, as an SSc susceptibility gene (10)(11)(12)(13)(14)(15). IRFs were identified primarily in the research of the type I IFN system and have been shown to have functionally diverse roles in the regulation of the innate and adaptive immune responses (16).…”
mentioning
confidence: 99%
“…As in the case of SLE, polymorphisms in the genes encoding proteins involved in the activation or activity of type I IFNs are also associated with a predisposition to develop certain of these diseases. For example, polymorphisms in the STAT4 and IRF5 genes are associated with an increased risk of developing systemic sclerosis, an autoimmune connective tissue disorder characterized by fibrosis of multiple organs and a type I IFN signature [Dieude et al 2009;Ito et al 2009;Rueda et al 2009]. …”
Section: Therapeutic Advances In Drug Safety 2 (3)mentioning
confidence: 99%
“…Given the key role played by type I IFNs in the innate immune response it is perhaps not surprising that dysregulation of the type I IFN pathway can under certain circumstances lead to induction or exacerbation of autoimmune disease in predisposed individuals [Burdick et al 2009]. Thus, polymorphisms in the genes encoding key intermediates in the type I IFN pathway have been identified as risk factors for the development of autoimmune disease [Dieude et al 2009;Ito et al 2009;Rueda et al 2009], and a number of IFN-induced proteins are up regulated in active disease [Ronnblom et al 2006;Baechler et al 2003]. Furthermore, a recent report has shown that a loss of function variant in the gene encoding MAVS, a key antiviral molecule downstream of the cytosolic doublestranded RNA sensors RIG-I and MDA-5, is associated with low type I IFN production and the absence of anti-RNA-binding protein autoantibodies in a novel subphenotype of SLE [Pothlichet et al 2011].…”
Section: Adverse Events: Underlying Mechanisms and Clinical Implicationsmentioning
confidence: 99%